Exposure to second-hand smoke among adolescent in secondary school students in Sana’a, Yemen - Al-Emad, Fateh Addin Nejm Addin; Zaleha Md. Isa, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction The aim of the study was to assess the knowledge and attitude of secondary school students in Sana'a Yemen related to exposure to second-hand smoking. Methods A cross-sectional study was conducted in Sana'a city. The total sample size was 336 students in which 63 were males and 273 were females. These students were stratified random sampling. Data were collected by using Questionnaire comprising of 3 parts: Part 1- consists of socio-demographic data. Part 2- consists of the knowledge regarding smoking and second-hand smoking and Part 3-consists of adolescents' attitude in relation to second-hand smoking. Results Out of 336 students, majority were between 14-18 years old (75.9%), males (81.2%) , (55.7%)of them was fathers' occupation private employee and low educated mother was (86.3%).The students who do not have smoking habit were (94.3%),and those who do not have friends with the habit of smoking was (57.4%). (57.10) having some one else at home who smokes beside them .The reaction of non printed mass media for SHS warning was (83.3%). The exposed to smoke out door was (60.1%). In this study, the majority of students had inadequate knowledge about the second-hand smoke was (52.7%). A higher percentage of students who had unfavorable attitudes toward secondhand smoke was (86.6%). Conclusions We concluded that The level of knowledge and attitude about the second-hand smoke is relatively low among the secondary school student in Sana'a Yemen. The finding of this study emphasized the need of effective awareness programs to increase level of consciousness and knowledge regarding SHS.